CONTINUOUS ANAEROBIC BIODIGESTION OF THE LIQUID SUBSTRATE EXTRACTED FROM PINEAPPLE STUBBLE IN BIODIGESTERS OF 0.1 AND 4.6 L - Alberto MIRANDA CHAVARRIA; Werner RODRÍGUEZ; Carlos SABORÍO-VIQUEZ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The pineapple crop represents the most important agricultural activity in Costa Rica, from the economic point of view, represents 32% of agricultural exports. The sowing area is estimated at 58,000 hectares. However, this activity generates a considerable amount of biomass in the order of 340 metric tons per hectare, of which 26% corresponds to fruit and 74% to organic agricultural waste (OAW), so called pineapple stubble. This is a generator of environmental problems because it is not treated adequately in the field, where it is opted for the use of herbicides to cause its degradation and then incorporate it into the soil, a practice that has generated problems of contamination of groundwater and the pest of the stable fly Stomoxys Calcitrans. The stubble of the pineapple has the highest energy potential, within the OAW that are generated in the agricultural activity in the country as mentioned by Coto in 2013. The use of pineapple stubble juice was evaluated as a substrate for biodigestion in mesophilic conditions, using the Hohenheim methodology with volumes of 100 ml and in 6 liters CSTD biodigesters. Three types of substrate were evaluated: 100% stubble juice, a mixture of 90% juice and 10% cow manure and a mixture of 80% juice and 20% cow manure. The substrate of 100% pure pineapple stubble juice showed the best performance in biogas production. In the Hohenheim test the accumulated production was 320 ml, while the 9010 mixture produced 280 ml and the mixture 80 -20 produced 250 ml. In the CSTD reactor test, the substrate 100% stubble juice had an accumulated production of 170 liters; the 90-10 mixture produced 60 liters. The 80-20 mixture collapsed from day 20, ceasing gas production. The behavior of the pH and the FOS/TAC test showed stable behavior during the process in all cases. It was demonstrated that pure stubble juice is a good substrate for the biodigestion process; with which the technology of anaerobic biodigestion is presented as an important alternative for the use of this kind of OAW.